SEEKING SELF THROUGH FASHION: HOW SELF-DETERMINATION DRIVES LUXURY APPAREL PURCHASES IN EMERGING ECONOMIES - Ekta Aggarwal; Richa Misra; Renuka Mahajan; Anurupa B Singh (International Journal of Management Studies)
Luxury brands are gaining popularity in both developed and emerging economies. Recent research has advocated wider use of self-determination theory (SDT) in marketing studies, suggesting that it has high predictive accuracy for understanding consumer motivations. Underpinned by this particular theory, this study aims to measure the impact of intrinsic motivations (brand commitment, hedonic motivation, and self-congruity) and extrinsic motivations (social motivation) on the purchasing intention of luxury fashion apparel brands in a developing country. Data was collected from 490 luxury apparel brand users, utilizing both offline and online modes via survey questionnaires. The proposed relationships were analyzed using PLS-SEM. Intrinsic motivations (brand commitment, hedonic motivation) and extrinsic motivation factor (social motivation) positively impacted purchase intention of luxury fashion apparel, while the impact of self-congruity (intrinsic motivator) was insignificant. This study adds to the body of knowledge about luxury branding by reassessing and expanding SDT with a new set of intrinsic and extrinsic motivations in collectivist society. The present study is among very few studies in marketing science that explicitly applied SDT. The uniqueness of this study is that it empirically examines consumer behavioral differences towards luxury buying in the luxury fashion apparel segment, utilizing SDT. Therefore, it is a major addition to the body of literature in the area. The findings of the study provide marketers with practical insights into luxury customer behavior, enabling them to target consumers in a growing economy, making them a high-potential market.